P-647 Intake of soy foods and soy isoflavones in relation to ovarian reserve among women presenting to a fertility center. (30th June 2022) - Mitsunami, M; Mínguez-Alarcón, L; Souter, I; Hauser, R; Chavarro, J
Abstract: Study question: Are soy food and isoflavone intakes associated with ovarian reserve as measured by antral follicle count (AFC)? Summary answer: Within the observed range of intake, soy food or isoflavone consumptions are not associated with AFC. What is known already: Phytoestrogens are structurally similar to 17β-estradiol, and bind to ER-α and ER-β in vitro resulting in weak estrogenic activity. Previous work in ruminants, felines and rodents has shown that exposure to phytoestrogens can have major adverse impacts on reproduction. However, findings of studies in humans suggest that soy foods and soy phytoestrogens may not have major deleterious impacts on reproductive hormone levels or reproductive outcomes, and could even be beneficial in couples undergoing infertility treatment. Study design, size, duration: Women presenting to a large academic fertility center between April 2007 and December 2019 were invited to participate in the Environment and Reproductive Health (EARTH) Study, a prospective cohort study. Intake of 15 soy-based foods during the previous three months was obtained at baseline and intake of soy phytoestrogens was estimated from these reports. AFC was assessed with transvaginal ultrasound performed as part of diagnostic evaluation for infertility. Participants/materials, setting, methods: We included 667 women who reported their soy food intake and had an AFC assessment. Women were divided in groups of increasing soy food and soy isoflavone intake with women who reported not consuming soy-based foods serving as the reference group. We evaluated the association of soy foods and soy isoflavones intake with AFC using Poisson regression models adjusting for confounders. Analyses were also stratified by age, BMI, and smoking status. Main results and the role of chance: Women had median baseline age of 35.0 years and BMI of 23.4 kg/m 2 . Mean (range) intake of soy foods was 0.1 (0-7.4) servings/day, and mean (range) intake of isoflavones was 6 (0-166) mg/day, which is comparable to that of women in the general population of the USA. Intakes of soy foods or isoflavones were not related to AFC. The median (IQR) AFC for women who did not consume soy foods and women in the highest category of soy intake (>0.45 servings/day, median 0.88 servings/day) were 12 (9, 18) and 13 (9, 19). After adjustment for potential confounders, the mean difference in AFC between women in the highest category of soy intake and women who did not consume soy was -0.5% (-6.6%, 6.1%). Soy food intake remained unrelated to AFC when intake was categorized using different cutoff values when intake was modeled as a continuous variable when departures from a linear association were considered, and when we excluded from analysis 76 women whose AFC ultrasound scan was performed before they completed the diet assessment. Soy intake was also unrelated to AFC within categories of age, BMI and smoking status. Findings for soy isoflavones mirrored those for soy-food intake. Limitations, reasons for caution: Self-reported soy intake may have resulted in measurement error leading to attenuation of observed relations towards the null. Also, all participants were women presenting to a fertility center and therefore, findings may not be generalizable to women in the general population. Wider implications of the findings: Our findings suggest soy food and isoflavone intakes within the ranges observed among women in the general population of the USA is unlikely to influence ovarian reserve in any meaningful way. Trial registration number: Not applicable